The blacklist. The complete fifth season [videorecording (DVD)]. - Boone, Megan, 1983-; Spader, James; Klattenhoff, Diego (Sony Pictures Home Entertainment, 2018)
Feeling surprisingly unencumbered, Raymond Reddington is back, and in the process of rebuilding his criminal empire. Liz finds herself torn between her role as an FBI agent and the temptation to act on her more criminal instincts. In a world where the search for Blacklisters has become a family trade, Red will undoubtedly reclaim his moniker as the 'Concierge of Crime.'